High-strength ferritic stainless steel for clamping device and method for manufacturing the same

By controlling the content of elements such as Si, Al, V, C, N and omitting hot rolling annealing, combined with the light-cleaning cold rolling process, the shortcomings of ferrite stainless steel in terms of yield strength and elongation are solved, and high-strength ferrite is achieved Body stainless steel, suitable for clamping devices of automobiles or general hoses.

CN114945689BActive Publication Date: 2025-02-25POHANG IRON & STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080093046.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-11-11
Publication Date
2025-02-25
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Existing ferrite stainless steels are difficult to meet high strength requirements such as 350MPa or greater, 510MPa or greater and 20% or greater in terms of yield strength and elongation, especially in clamping devices for automobiles or general hoses. .

Method used

By controlling the content of elements such as Si, Al, V, C, N in the slab, and omitting hot rolling annealing, the photo-pairing cold rolling process is used to control the size and amount of precipitates, satisfying the specific component system and manufacturing process.

Benefits of technology

The high-strength ferrite stainless steel has achieved a yield strength of 350MPa or greater, a tensile strength of 510MPa or greater and an elongation of 20% or greater, and is suitable for high-demand clamping devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114945689B_ABST
    Figure CN114945689B_ABST
Patent Text Reader

Abstract

Disclosed are high-strength ferritic stainless steel STS430 having a yield strength of 350 MPa or more and being applicable to a clamping device for a vehicle or a general hose and a method for manufacturing the same. According to one embodiment of the present invention, the high-strength ferritic stainless steel for a clamping device comprises, by weight %, 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.02% to 0.1% N, and the balance of Fe and unavoidable impurities, satisfying formulas (1) and (2), and having at least 2.5×10 6 Pieces / mm 2 The average diameter of the precipitates is 0.5 μm or less. (1) 0.35% ≤ Si + Al + V ≤ 0.6% (2) 0.09% ≤ C + N ≤ 0.12%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to high-strength ferritic stainless steel and a method for manufacturing the same, and more particularly, to high-strength ferritic stainless steel having a yield strength of 350 MPa or more and applicable to a clamping device for an automobile or a general hose and a method for manufacturing the same. Background Art

[0002] Ferritic stainless steel is widely used in heat-resistant equipment, sink countertops, exterior materials, home appliances, electronic components, etc. due to its low price, low thermal expansion coefficient, good surface gloss, good formability and good oxidation resistance compared to austenitic stainless steel. The cold-rolled thin sheet of ferritic stainless steel is manufactured by a hot rolling process, an annealing and pickling process to remove the surface scale of the hot-rolled coil and eliminate the internal stress of the material, a cold rolling process and an annealing process.

[0003] Figure 1 A clamp for an automobile or general hose is shown. The clamp requires high strength because it is used to fix a plastic hose or pipe, and also requires excellent ductility because cracks should not exist during bending. In addition, since it is used not only inside but also outside of an automobile, corrosion resistance is required, so the demand for stainless steel used for the clamp is increasing recently.

[0004] Commonly manufactured general-purpose ferrites such as 410UF have poor corrosion resistance and low elongation due to their 12% Cr content, so they may not be used for clamping devices. Therefore, attempts were made to use the 16%Cr430 series (generally 430, 430LX) with a relatively high Cr content, but it was difficult to meet market demand due to low tensile strength. In order to meet market demands including a tensile strength (TS) of 510 MPa or more, a yield strength (YS) of 350 MPa or more, and an elongation (El) of 20% or more in all three directions of 0°, 45°, and 90° based on the rolling direction, component system development and manufacturing process optimization are required.

[0005] For the main quality issues of ferritic stainless steel exemplified by STS430, there are many existing patent technologies related to the improvement of wrinkling, orange peel and in-plane anisotropy during forming. However, there is almost no research on optimizing manufacturing technology and examining component systems that meet high strength so that it can be applied to clamping devices for automobiles or general hoses. Summary of the invention

[0006] Technical issues

[0007] The present invention aims to provide STS430 ferritic stainless steel and a method for manufacturing the same: the STS430 ferritic stainless steel can achieve high strength, for example, a yield strength of 350 MPa or more, by controlling the contents of Si, Al, V, C, N, etc. in the component system, and by controlling the size and amount of precipitates by omitting hot rolling annealing and performing skin-pass cold rolling.

[0008] Technical Solution

[0009] One aspect of the present invention provides a method for manufacturing high-strength ferritic stainless steel for a clamping device, the method comprising: hot rolling a slab by reheating at 1,000° C. to 1,200° C., the slab comprising, by weight: 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.01% to 0.2% Sr ... .02% to 0.1% N, and Fe and inevitable impurities in the remainder, and satisfying the following expressions (1) and (2); coiling the hot-rolled steel sheet at 700°C or higher; cold rolling the coiled hot-rolled steel sheet at a reduction ratio of 60% or more without annealing; annealing the cold-rolled steel sheet at 550°C to 950°C for 10 minutes or less; and skin-pass rolling the cold-rolled annealed steel sheet at a reduction ratio of 2% to 8%.

[0010] (1) 0.35%≤Si+Al+V≤0.6%

[0011] (2) 0.09%≤C+N≤0.12%

[0012] Here, Si, Al, V, C and N refer to the content (weight %) of each element.

[0013] According to one embodiment of the present invention, the cold-rolled annealed steel sheet may include at least 2.5×10 6 Pieces / mm 2 (Cr,Fe)-carbonitride precipitates having an average diameter of 0.5 μm or less.

[0014] According to one embodiment of the present invention, the slab may further include any one or more selected from the group consisting of 0.001% to 0.5% of Ni, 0.05% or less of P, and 0.005% or less of S.

[0015] According to one embodiment of the present invention, the cold-rolled annealed steel sheet may have a yield strength of 320 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more.

[0016] According to one embodiment of the present invention, the cold-rolled annealed steel sheet may have a yield strength of 350 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more by performing skin pass rolling.

[0017] Another aspect of the present invention provides a high-strength ferritic stainless steel for a clamping device, comprising, by weight, 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.02% to 0.1% N, and Fe and unavoidable impurities in the remainder, satisfies the following expressions (1) and (2), and has a yield strength of 350 MPa or more.

[0018] (1) 0.35%≤Si+Al+V≤0.6%

[0019] (2) 0.09%≤C+N≤0.12%

[0020] According to one embodiment of the present invention, the high-strength ferritic stainless steel may further include any one or more selected from the following: 0.001% to 0.5% Ni, 0.05% or less P, and 0.005% or less S.

[0021] According to one embodiment of the present invention, at least 2.5×10 6 Pieces / mm 2 (Cr,Fe)-carbonitride precipitates having an average diameter of 0.5 μm or less.

[0022] According to one embodiment of the present invention, the high-strength ferritic stainless steel may have a tensile strength of 510 MPa or more and an elongation of 20% or more.

[0023] Beneficial Effects

[0024] The high-strength ferritic stainless steel according to one embodiment of the present invention can be used for a clamping device of an automobile or the like by satisfying a yield strength of 350 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an image showing the shape of a general clamping device.

[0026] Figure 2 : is a graph showing the yield strength (YS) before skin-pass rolling according to the present invention as a function of the value of expression (1).

[0027] Figure 3 : is a graph showing the tensile strength (TS) before skin-pass rolling according to the present invention as a function of the value of expression (2).

[0028] Figure 4 The figures show photographs of precipitates of the inventive examples and comparative examples according to the present invention, taken using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). DETAILED DESCRIPTION

[0029] A method for manufacturing high-strength ferritic stainless steel for a clamping device according to an embodiment of the present invention comprises: hot rolling a slab by reheating at 1,000° C. to 1,200° C., the slab comprising, by weight: 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0. 0.02% to 0.1% N, and Fe and inevitable impurities in the remainder, and satisfying the following expressions (1) and (2); coiling the hot-rolled steel sheet at 700° C. or higher; cold rolling the coiled hot-rolled steel sheet at a reduction ratio of 60% or more without annealing; annealing the cold-rolled steel sheet at 550° C. to 950° C. for 10 minutes or less; and skin-pass rolling the cold-rolled annealed steel sheet at a reduction ratio of 2% to 8%.

[0030] (1) 0.35%≤Si+Al+V≤0.6%

[0031] (2) 0.09%≤C+N≤0.12%

[0032] Here, Si, Al, V, C and N refer to the content (weight %) of each element.

[0033] Embodiments of the invention

[0034] Hereinafter, exemplary embodiments of the present invention will be described in detail with reference to the accompanying drawings. The exemplary embodiments presented herein are provided to fully convey the spirit and scope of the present invention to those skilled in the art. The present invention can be implemented in various forms without being limited to the embodiments presented herein. In the accompanying drawings, in order to make the present invention clear, parts irrelevant to the description may be omitted, and the size of the components may be magnified in order to understand the present invention.

[0035] The high-strength ferritic stainless steel for a clamping device according to one embodiment of the present invention contains, by weight, 0.04% to 0.1% of C, 0.2% to 0.6% of Si, 0.01% to 1.5% of Mn, 14.0% to 18.0% of Cr, 0.005% to 0.2% of Al, 0.005% to 0.2% of V, 0.02% to 0.1% of N, and Fe and inevitable impurities in the remainder.

[0036] Hereinafter, the reason for limiting the numerical value of the alloy element content of the present invention will be described. Hereinafter, unless otherwise specified, the unit is weight %.

[0037] The C content is 0.04% to 0.1%.

[0038] In steel, C is an impurity inevitably contained in ferritic stainless steel and is used as (Cr, Fe) 23 C6 and (Cr,Fe)7C3 carbides precipitate to improve strength, so C is contained in an amount of 0.04% or more. However, when C is excessively contained in the base material, elongation decreases to substantially reduce workability of the product, so the C content is limited to 0.1% or less.

[0039] The content of Si is 0.2% to 0.6%.

[0040] Si is an impurity inevitably contained in steel, but is an element added as a deoxidizer during steelmaking, and is a ferrite stabilizing element. When a large amount of Si is contained in steel, it causes hardening of the material to reduce ductility, so the Si content is generally controlled to 0.4% or less. However, in order to manufacture high-strength ferritic stainless steel for clamping devices, it is necessary to use Si optimally. Therefore, in the present invention, the Si content is controlled to 0.2% to 0.6% to improve tensile strength and yield strength by solid solution strengthening effect, and the Si content is limited to 0.6% or less in order to maintain elongation.

[0041] The content of Mn is 0.01% to 1.5%.

[0042] Mn is an impurity inevitably contained in steel. However, since Mn is an austenite stabilizing element, it is used to suppress ridges and wrinkles. However, when a large amount of Mn is contained, manganese-based smoke is generated during welding, and the smoke causes precipitation of a MnS phase to reduce elongation, so the Mn content is limited to 0.01% to 1.5%.

[0043] The Cr content is 14.0% to 18.0%.

[0044] Cr is an alloy element added to improve the corrosion resistance of steel, and its critical content is 12%. However, ferritic stainless steel containing C and N may experience intergranular corrosion, so the Cr content is limited to 14.0% to 18.0% in consideration of the possibility of intergranular corrosion and the increase in manufacturing cost.

[0045] The content of Al is 0.005% to 0.2%.

[0046] Al is a strong deoxidizer and is used to reduce the oxygen content in molten steel. In the present invention, Al is added in an amount of 0.005% or more. However, when the Al content is too much, sleeve defects of the cold-rolled steel strip occur due to the increase of non-metallic inclusions, and weldability also deteriorates, so the Al content is limited to 0.2% or less, more preferably 0.1% or less.

[0047] The content of V is 0.005% to 0.2%.

[0048] V is used to form carbonitrides by fixing C and N, and is an element effective for suppressing the growth of carbonitrides and refining them. In the present invention, V is added in an amount of 0.005% or more, more preferably 0.03% or more. However, when the V content is too much, the manufacturing cost increases rapidly, so the V content is limited to 0.2% or less, more preferably 0.1% or less.

[0049] The content of N is 0.02% to 0.1%.

[0050] In steel, N exists as an impurity element equivalent to C, and serves to improve strength by precipitating as Cr2N nitride during the manufacturing process. N is added in an amount of 0.02% or more. However, a large amount of N addition not only impairs workability but also causes tensile strain in cold-rolled products, so the N content is limited to 0.1% or less.

[0051] Furthermore, according to one embodiment of the present invention, the high-strength ferritic stainless steel may further include any one or more selected from the following: 0.001% to 0.5% Ni, 0.05% or less P, and 0.005% or less S.

[0052] The content of Ni is 0.001% to 0.5%. Similar to Cu and Mn, Ni is an austenite stabilizing element, has the effect of suppressing ridges and wrinkles by increasing the austenite fraction, and is used to improve corrosion resistance by adding a small amount of Ni. However, when a large amount of Ni is added, it causes deterioration of workability and increase in manufacturing cost, so the Ni content is limited to the above range.

[0053] The content of P is 0.05% or less. P is an impurity inevitably contained in steel, and causes intergranular corrosion during pickling or impairs hot workability, so the P content is adjusted within the above range.

[0054] The content of S is 0.005% or less. S is an impurity inevitably contained in steel, and segregates at grain boundaries to impair hot workability, so the S content is limited to the above range.

[0055] In addition to the above alloying elements, stainless steel also contains Fe and other inevitable impurities in the remainder.

[0056] Furthermore, the stainless steel satisfies the following expressions (1) and (2) and the above-mentioned component system composition.

[0057] (1) 0.35%≤Si+Al+V≤0.6%

[0058] (2) 0.09%≤C+N≤0.12%

[0059] In the present invention, in order to achieve high strength, the yield strength (YS) is increased by the solid solution strengthening effect caused by the increase in the content of Si, Al and V as substitute elements, so that 320 MPa or more can be exhibited. When the Si+Al+V value is less than 0.35%, it is difficult to achieve the desired yield strength, and when the Si+Al+V value exceeds 0.6%, the elongation decreases. In addition, as in the manufacturing method to be described below, the annealed cold-rolled steel sheet can be subjected to skin-pass rolling to achieve a yield strength of 350 MPa or more. When the yield strength before skin-pass rolling is lower than 320 MPa, a high reduction rate is required during skin-pass rolling, which leads to a decrease in elongation, so this situation is not preferred. Therefore, it is important to ensure a yield strength of 320 MPa or more by satisfying expression (1) before skin-pass rolling.

[0060] By increasing the amount of (Fe,Cr) carbonitride precipitates by increasing the C+N content, and by increasing the amount of work hardening by the refinement of the precipitates caused by omitting hot rolling annealing, a tensile strength (TS) of 510 MPa or more can be achieved. When the C+N value is less than 0.09%, it is difficult to achieve the desired tensile strength, and when the C+N value exceeds 0.12%, the elongation decreases.

[0061] According to the above alloying element control, the microstructure of the present invention may contain at least 2.5×10 6 Pieces / mm 2 The average diameter of (Fe,Cr)-carbonitride precipitates is 0.5μm or less. As the C+N content increases, the (Fe,Cr)-carbonitride precipitates can be (Cr,Fe) 23C6 and (Cr,Fe)7C3 carbides or Cr2N nitrides. By precipitating a large number of fine precipitates having an average diameter of 0.5 μm or less, the amount of work hardening during drawing can be increased.

[0062] However, in order to precipitate (Fe,Cr)-carbonitrides, in addition to alloying element control, it is necessary to omit hot rolling annealing.

[0063] In the case of a clamp for connecting a hose, when the hose has a small diameter, a clamp having a thickness of 1 mm or less is used, and a yield strength (YS) of 320 MPa or more is required, while when the hose has a large diameter, a clamp having a thickness of 1 mm or more is used, and a yield strength (YS) of 350 MPa or more is required. By controlling the above-mentioned alloy elements and carbonitride precipitates, a yield strength (YS) of 320 MPa or more can be ensured, but it is difficult to ensure a yield strength (YS) of 350 MPa or more. Therefore, in order to achieve a yield strength of 350 MPa or more, it is necessary to improve the manufacturing method.

[0064] A method for manufacturing high-strength ferritic stainless steel for a clamping device according to an embodiment of the present invention comprises: hot rolling a slab by reheating at 1,000° C. to 1,200° C., the slab comprising, by weight: 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.01% to 0.2% Mn, 0.02% to 0.0 ...2% to 0.06% Mn, 0.02% to 0.06% Mn, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.01% to 0.2% Mn, 0.01% to 1.5% Mn, 0.02% to 0.06% .02% to 0.1% N, and Fe and inevitable impurities in the remainder, and satisfying expressions (1) and (2); coiling the hot rolled steel sheet at 700°C or higher; cold rolling the coiled hot rolled steel sheet at a reduction ratio of 60% or more without annealing; annealing the cold rolled steel sheet at 550°C to 950°C for 10 minutes or less; and skin pass rolling the cold rolled annealed steel sheet at a reduction ratio of 2% to 8%.

[0065] The hot rolling finishing temperature is preferably 800° C. or higher. Fine precipitates are formed in a state where a hot rolled coil is rolled at a finishing temperature of 800° C. or higher and coiled at 700° C. or higher, and coarsening of the precipitates is prevented by omitting subsequent hot rolling annealing.

[0066] Generally, ferritic stainless steel for clamping devices is subjected to batch annealing (batch annealing furnace (BAF)) as hot rolling annealing after hot rolling, but the present invention is characterized in that hot rolling annealing is omitted. When batch annealing (BAF) is performed, fine precipitates precipitated in the hot rolled coil become coarse and their total amount decreases, making it difficult to ensure high strength.

[0067] The cold-rolled annealed steel sheet may be subjected to skin-pass rolling at a reduction rate of 2% to 8% to ensure a yield strength of 350 MPa or more. When the reduction rate exceeds 8%, the elongation decreases.

[0068] Hereinafter, the present invention will be described in further detail with reference to exemplary embodiments.

[0069] Example

[0070] Ferritic stainless steel having a component system in which C, N, Si, Al and V were controlled as shown in Table 1 below was subjected to laboratory vacuum melting to prepare a slab. The slab was reheated at 1,000 to 1,200° C. and then rolled at a finishing temperature of 800° C. or higher using a roughing mill and a continuous finishing mill to produce a hot-rolled plate.

[0071] [Table 1]

[0072]

[0073] The hot rolled sheet is subjected to cold rolling and annealing, and then some steel grades are subjected to skin pass rolling to produce a final cold rolled sheet.

[0074] Table 2 below shows the values ​​of expressions (1) and (2) defined as Si+Al+V and C+N, respectively, for the steels having the alloy components shown in Table 1, and also shows the hot rolling annealing conditions and the number of precipitates of the cold rolled annealed material. In addition, the yield strength (YS), tensile strength (TS) and elongation (EL) obtained by conducting a tensile test at room temperature and on the plate surface of the cold rolled annealed material at a crosshead speed of 20 mm / min in the 0° direction from the rolling direction are shown.

[0075] [Table 2]

[0076]

[0077] Invention Examples 1 and 2

[0078] Steel grades A and B are obtained by controlling C, N, Si, Al and V of ferritic stainless steel by vacuum melting, and each steel is reheated at 1,000° C. to 1,200° C. and then rolled at a finishing temperature of 800° C. or higher using a roughing mill and a continuous finishing mill to manufacture a hot-rolled plate, and then the hot-rolled plate is subjected to pickling, cold rolling, cold annealing and skin-pass rolling without hot rolling annealing.

[0079] It can be determined that steel grades A and B satisfy Si+Al+V≥0.35% and satisfy yield strength (YS)≥350MPa by skin-pass rolling. In addition, it can be determined that steel grades A and B satisfy C+N≥0.09% and thus satisfy tensile strength (TS)≥510MPa.

[0080] Comparative Examples 1 to 3

[0081] It can be determined that steel grades C to E satisfy expression (1) of the present invention, for example, have a C+N value of 0.09% or more, but a Si+Al+V value of 0.35% or less, and therefore exhibit a yield strength (YS) of 300 MPa, and the yield strength (YS) is as low as 320 MPa before skin-pass rolling.

[0082] Comparative Examples 4 and 5

[0083] It was determined that Steel Types F and G exhibited Si+Al+V values ​​of 0.35% or less and C+N values ​​of 0.09% or less, and therefore both yield strength (YS) and tensile strength (TS) did not satisfy the desired levels of the present invention even after skin-pass rolling.

[0084] Comparative Examples 6 and 7

[0085] It can be determined that steel type H satisfies a Si+Al+V value of 0.35% or more and a C+N value of 0.09% or more, but cannot satisfy a yield strength (YS) ≥ 320 MPa and a tensile strength (TS) ≥ 510 MPa by performing hot rolling batch annealing (BAF).

[0086] Furthermore, it can be determined that Steel Type I does not satisfy the Si+Al+V value of 0.35 or more and the C+N value of 0.09% or more, and exhibits a low yield strength (YS) of 280 MPa or less by performing hot rolling batch annealing (BAF), and also exhibits a low tensile strength (TS) of 490 MPa or less, and thus cannot satisfy the desired strength level of the present invention.

[0087] Figure 2 is a graph showing the yield strength (YS) before skin-pass rolling according to the present invention as a function of the value of expression (1), Figure 3 : is a graph showing the tensile strength (TS) before skin-pass rolling according to the present invention as a function of the value of expression (2).

[0088] Reference Figure 2 and Figure 3In the present invention, in order to achieve high strength, the value of expression (1) defined as Si+Al+V as the sum of the substitution elements is controlled to 0.35% or more to improve the yield strength by the solid solution strengthening effect of the substrate, so that a yield strength of 320 MPa or more can be achieved. In addition, the desired yield strength of 350 MPa or more can be ensured by performing skin-pass cold rolling. In addition, the value of expression (2) defined as C+N is controlled to 0.09% or more to increase the amount of (Fe,Cr)-carbonitride precipitates, and the hot rolling annealing process is omitted to provide a precipitate refinement effect and thus increase the amount of work hardening, so a tensile strength of 510 MPa or more can be achieved.

[0089] Figure 4 The photographs of precipitates of the inventive examples and comparative examples according to the present invention taken using a scanning electron microscope (SEM) and a transmission electron microscope (TEM) are shown. The Unannealed column shows a photograph of Steel Type A of Inventive Example 1, and the BAF column shows a photograph of Steel Type I of Comparative Example 7.

[0090] It can be confirmed that in the case of Steel Type A of Inventive Example 1, a large number of precipitates with an average diameter of 0.5 μm or less are formed, while in the case of Steel Type I of Comparative Example 7, precipitates with an average diameter of 0.5 μm to 2.0 μm are formed. That is, it can be seen that the object of the present invention can be achieved when both the control of the alloy composition and the omission of hot rolling annealing are satisfied.

[0091] As described above, exemplary embodiments of the present invention have been described, but the present invention is not limited thereto, and those skilled in the art will appreciate that various changes and modifications may be made to the exemplary embodiments of the present invention without departing from the concept and scope of the appended claims.

[0092] Industrial Applicability

[0093] The ferritic stainless steel according to the present invention can ensure a yield strength of 350 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more, and thus can be applied to clamping devices for automobiles or general hoses.

Claims

1. A method for manufacturing high-strength ferritic stainless steel for a clamping device, the method comprising: A slab is hot rolled by reheating at 1,000° C. to 1,200° C., the slab comprising, by weight, 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.02% to 0.1% N, and Fe and inevitable impurities in the remainder, and satisfies the following expressions (1) and (2); Coiling the hot-rolled steel sheet at 700° C. or higher; cold rolling the coiled hot-rolled steel sheet at a reduction ratio of 60% or more without annealing; Annealing the cold rolled steel sheet at 550°C to 950°C for 10 minutes or less; and The cold-rolled annealed steel sheet is subjected to skin pass cold rolling at a reduction rate of 2% to 8%. The cold-rolled annealed steel sheet comprises at least 2.5×10 6 Pieces / mm 2 (Cr,Fe)-carbonitride precipitates with an average diameter of 0.5 μm or less, (1) 0.35%≤Si+Al+V≤0.6% (2) 0.09% ≤ C + N ≤ 0.12% Here, Si, Al, V, C and N refer to the content (weight %) of each element. 2 . The method according to claim 1 , wherein the slab further comprises any one or more selected from the group consisting of 0.001% to 0.5% Ni, 0.05% or less P, and 0.005% or less S. 3 . The method according to claim 1 , wherein the cold-rolled annealed steel sheet has a yield strength of 320 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more. 4 . The method according to claim 1 , wherein the cold-rolled annealed steel sheet has a yield strength of 350 MPa or more, a tensile strength of 510 MPa or more, and an elongation of 20% or more after being subjected to skin-pass rolling.

5. A high-strength ferritic stainless steel for a clamping device, comprising, by weight, 0.04% to 0.1% C, 0.2% to 0.6% Si, 0.01% to 1.5% Mn, 14.0% to 18.0% Cr, 0.005% to 0.2% Al, 0.005% to 0.2% V, 0.02% to 0.1% N, and Fe and unavoidable impurities in the remainder, satisfying the following expressions (1) and (2), and having a yield strength of 350 MPa or more, The high-strength ferritic stainless steel comprises (Cr, Fe)-carbonitride precipitates, in which at least 2.5×10 6 Pieces / mm 2 (Cr,Fe)-carbonitride precipitates with an average diameter of 0.5 μm or less, (1) 0.35%≤Si+Al+V≤0.6% (2) 0.09% ≤ C + N ≤ 0.12% in, Si, Al, V, C and N refer to the content (weight %) of each element. 6 . The high-strength ferritic stainless steel according to claim 5 , further comprising any one or more selected from the following: 0.001% to 0.5% of Ni, 0.05% or less of P, and 0.005% or less of S. 7 . The high-strength ferritic stainless steel according to claim 5 , having a tensile strength of 510 MPa or more and an elongation of 20% or more.

Citation Information

Patent Citations

  • Cold-rolled ferritic stainless steel sheet

    CN106795601A